CoP-coated CoFeP-coated CC electrocatalyst and preparation method thereof
Through the preparation method of CoP@CoFeP@CC electrocatalyst, the problem of insufficient electron transfer capacity of transition metal phosphides at the solid-liquid interface is solved, the conductivity and catalytic activity of the catalyst are improved, and the catalytic performance is improved and the stability of catalytic performance is achieved.
Patent Information
- Application Number
- CN202411691137.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-01-07
AI Technical Summary
The electron transfer capacity of transition metal phosphides in the solid-liquid interface in the field of electrocatalytic water cracking affects the improvement of catalytic performance, and insufficient boundary electron replenishment and mass transfer barriers exist.
Using the preparation method of CoP@CoFeP@CC electrocatalyst, Co(NO3)2·6H2O, Fe(NO3)3·9H2O, urea and NH4F are dissolved in ultrapure water for hydrothermal reaction, forming the precursor CoFe(OH) @CC, and the ZIF layer was coated in a mixed solution of 2-methylimidazole and ethanol, and then phosphating annealing was performed in a hydrogen-argon mixture to form a CoP@CoFeP@CC electrocatalyst.
The conductivity and catalytic activity of the catalyst are improved, the electron transfer ability is enhanced, the mass transfer barrier is reduced, the catalytic efficiency and stability are improved, and the catalytic performance is continued.
Smart Images

Figure CN119265625A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of electrocatalysts, and in particular to a CoP@CoFeP@CC electrocatalyst and a preparation method thereof. Background Art
[0002] Transition metal phosphides (TMPs), as a new type of electrocatalyst, have shown remarkable performance in the field of electrocatalytic water splitting in recent years. For example, CoP and FeP have become the focus of researchers due to their unique electronic structure and good catalytic activity. They can not only effectively catalyze OER and HER reactions, but also perform well in terms of stability and durability.
[0003] Anion / cation doping and heterostructure construction are commonly used methods to improve the electrocatalytic performance of transition metal phosphides. By introducing other elements for doping, the electronic structure of TMPs can be optimized and the catalytic activity can be improved. The construction of heterostructures can further enhance the electron transport capacity, promote the adsorption of reactants and the desorption of products, thereby improving the catalytic efficiency.
[0004] Although transition metal phosphides have made progress in the field of electrocatalytic water splitting, there are still some shortcomings. Among them, the most prominent problem is that their electron transfer ability at the solid-liquid interface is still not ideal. This limits the electron transfer efficiency between the catalyst and the reactants, thus affecting the improvement of catalytic performance. In addition, insufficient boundary electron supplementation and mass transfer barriers are also problems that need to be solved at present.
[0005] Therefore, how to develop new preparation methods and modification strategies to improve the electrocatalytic performance of transition metal phosphides has become a problem to be solved. Summary of the invention
[0006] In the embodiments of the present application, a CoP@CoFeP@CC electrocatalyst and a preparation method thereof are provided to solve the problem of how to develop new preparation methods and modification strategies to improve the electrocatalytic performance of transition metal phosphides.
[0007] In the first aspect, an embodiment of the present application provides a method for preparing a CoP@CoFeP@CC electrocatalyst, comprising: dissolving Co(NO3)26H2O, Fe(NO3)39H2O, urea and NH4F in ultrapure water to obtain a transparent solution; performing carbon cloth pretreatment, placing the pretreated carbon cloth into the obtained transparent solution, and performing a hydrothermal reaction at 120°C to 160°C to obtain a precursor CoFe(OH)@CC; placing the precursor CoFe(OH)@CC into a second mixed solution of 2-methylimidazole and ethanol for 8 to 24 hours to obtain a precursor CoFe(OH)@CC with a ZIF coating layer, taking it out and placing it in an oven, and storing it at 40 to 80°C for 8 hours to obtain a precursor CoFe(OH)@ZIF@CC; in a hydrogen-argon mixture, performing a phosphating annealing treatment on a phosphorus source and a precursor CoFe(OH)@ZIF@CC at 250°C to 600°C to obtain a CoP@CoFeP@CC electrocatalyst.
[0008] Furthermore, the carbon cloth pretreatment includes: placing the carbon cloth in a nitric acid solution with a concentration of 0.5 to 4.0 mol / L, and ultrasonically washing the carbon cloth at a temperature of 40 to 80° C. for 2 to 6 hours; taking the carbon cloth out of the nitric acid solution, and ultrasonically washing it in ultrapure water and ethanol for 1 hour each; placing the washed carbon cloth in an oven at 60 to 80° C. and baking it for 1 hour to complete the carbon cloth pretreatment.
[0009] Furthermore, the pretreated carbon cloth is placed in the obtained transparent solution, and a hydrothermal reaction is carried out at 120°C to 160°C to obtain a precursor CoFe(OH)@CC, including: pouring the obtained transparent solution into a polytetrafluoroethylene-lined container in batches; placing the pretreated carbon cloth into a polytetrafluoroethylene-lined container containing a transparent solution; cleaning the carbon cloth in the polytetrafluoroethylene-lined container with ultrasound; placing the polytetrafluoroethylene-lined container containing the carbon cloth and the transparent solution into a stainless steel autoclave; placing the stainless steel autoclave in an oven, and a hydrothermal reaction is carried out at 120°C to 160°C for 5 to 10 hours; after the hydrothermal reaction is completed, the autoclave is naturally cooled to room temperature; the carbon cloth is rinsed with ethanol and deionized water in turn to remove residues on the surface; the rinsed carbon cloth is placed in an oven, and dried at a temperature of 50 to 100°C for 8 hours to obtain the precursor CoFe(OH)@CC.
[0010] Further, the precursor CoFe(OH)@CC is immersed in a second mixed solution of 2-methylimidazole and ethanol for 8 to 24 hours to obtain a precursor CoFe(OH)@CC with a ZIF coating layer, which is taken out and placed in an oven and stored at 40 to 80° C. for 8 hours to obtain a precursor CoFe(OH)@ZIF@CC, comprising: dissolving 2-methylimidazole in a first mixed solution containing water and ethanol, ensuring that the 2-methylimidazole is completely dissolved to form a second mixed solution; the second mixed solution The mass ratio of 2-methylimidazole, water and ethanol in the liquid is 1:5-8:5-8; the precursor CoFe(OH)@CC is placed in the second mixed solution, and the precursor CoFe(OH)@CC is soaked for 8-24 hours to obtain the precursor CoFe(OH)@CC with a ZIF coating layer; after the soaking, the precursor CoFe(OH)@CC is taken out from the second mixed solution, and placed in an oven, and stored at 40-80°C for 8 hours to obtain the precursor CoFe(OH)@ZIF@CC.
[0011] Furthermore, in a hydrogen-argon mixture, a phosphorus source and a precursor CoFe(OH)@ZIF@CC are subjected to a phosphating annealing treatment at 250°C to 600°C to obtain a CoP@CoFeP@CC electrocatalyst, comprising: placing a phosphorus source at an upstream position of a porcelain boat; placing a precursor CoFe(OH)@ZIF@CC at a downstream position of the porcelain boat; placing the porcelain boat containing the phosphorus source and the precursor CoFe(OH)@ZIF@CC in a tubular furnace, introducing argon and hydrogen to form a hydrogen-argon mixture; heating the tubular furnace at a rate of 3°C / min to 250°C to 600°C, and maintaining this temperature range for 2 to 5 hours, performing a phosphating annealing treatment to obtain a reaction system; and allowing the reaction system to naturally cool to room temperature in an argon environment to obtain a CoP@CoFeP@CC electrocatalyst.
[0012] Furthermore, the molar ratio of Co(NO3)26H2O:Fe(NO3)39H2O:urea:NH4F in the transparent solution is 2-3:1:8-12:8-12.
[0013] Furthermore, the phosphorus source includes one or more of NaH2PO2, red phosphorus, white phosphorus, and phosphorus trichloride.
[0014] In a second aspect, an embodiment of the present application provides a CoP@CoFeP@CC electrocatalyst, and the CoP@CoFeP@CC electrocatalyst is obtained by the preparation method of the first aspect.
[0015] One or more technical solutions provided in the embodiments of the present application have at least the following technical effects:
[0016] The present application embodiment provides a CoP@CoFeP@CC electrocatalyst and a preparation method thereof. By dissolving Co(NO3)26H2O, Fe(NO3)39H2O, urea and NH4F in ultrapure water and performing a hydrothermal reaction, a precursor CoFe(OH)@CC with a specific structure and composition is successfully synthesized and firmly loaded on a carbon cloth. This step ensures the high activity and stability of the catalyst. Further ZIF coating treatment not only increases the specific surface area of the catalyst, but also optimizes its pore structure, which is conducive to the diffusion of reactants and the release of products, thereby improving the catalytic efficiency. Phosphating annealing treatment converts the precursor CoFe(OH)@ZIF@CC into a composite structure of CoP and CoFeP with excellent conductivity and catalytic activity, further improving the performance of the catalyst. The phosphating CoP and CoFeP have good conductivity and can efficiently transfer electrons, thereby solving the problem of insufficient boundary electron supplementation. As a substrate material, the excellent conductivity of carbon cloth also provides a good electron transfer channel for the entire catalyst. The porous structure formed by the ZIF coating is conducive to the diffusion and adsorption of reactant molecules, as well as the desorption and diffusion of product molecules, thereby reducing the mass transfer barrier. This porous structure also increases the contact area between the catalyst and the reactants, improving the efficiency of the catalytic reaction. Through the designed preparation steps and optimized reaction conditions, the obtained CoP@CoFeP@CC electrocatalyst has excellent stability and durability. During the long-term catalytic reaction process, the catalyst can maintain the stability of its structure and composition, thereby ensuring the continuous performance of the catalytic performance. The problem of how to develop new preparation methods and modification strategies to improve the electrocatalytic performance of transition metal phosphides is solved. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments of the present application or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0018] Figure 1 A flow chart of a method for preparing a CoP@CoFeP@CC electrocatalyst provided in an embodiment of the present application;
[0019] Figure 2 An electron microscope image of the CoP@CoFeP@CC electrocatalyst provided in the examples of the present application;
[0020] Figure 3 This is a long-term stability test diagram of the CoP@CoFeP@CC electrocatalyst in OER provided in the examples of the present application;
[0021] Figure 4 X-ray diffraction comparison diagram of CoP@CoFeP@CC electrocatalyst provided in the examples of the present application;
[0022] Figure 5 Schematic diagram of the linear sweep voltammetric curves of HER and OER of the CoP@CoFeP@CC electrocatalysts obtained in Example 1, Example 2, Example 3 and Example 4 respectively provided in the embodiments of the present application in 1.0 M potassium hydroxide alkaline solution. DETAILED DESCRIPTION
[0023] Various exemplary embodiments of the present application are now described in detail. This detailed description should not be considered as limiting the present application, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present application.
[0024] It should be understood that the terms described in the present application are only for describing special embodiments and are not intended to limit the present application. In addition, for the numerical range in the present application, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present application. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0025] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art in the field described in the present application. Although the present application only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present application. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of any conflict with any incorporated document, the content of this specification shall prevail.
[0026] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present application description without departing from the scope or spirit of the present application. Other embodiments derived from the present application description will be apparent to those skilled in the art. The present application description and examples are exemplary only.
[0027] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0028] The present application embodiment provides a method for preparing a CoP@CoFeP@CC electrocatalyst, such as Figure 1 As shown, the method includes steps S101 to S103. Among them, Figure 1This is only an execution order shown in the embodiment of the present application, and does not represent the only execution order of a method for preparing a CoP@CoFeP@CC electrocatalyst. If the final result can be achieved, Figure 1 The steps shown may be performed in parallel or reversed.
[0029] S101: Dissolve Co(NO3)26H2O, Fe(NO3)39H2O, urea and NH4F in ultrapure water to obtain a transparent solution, perform carbon cloth pretreatment, place the pretreated carbon cloth into the obtained transparent solution, perform hydrothermal reaction at 120°C to 160°C, and obtain a precursor CoFe(OH)@CC.
[0030] The molar ratio in the transparent solution is Co(NO3)26H2O:Fe(NO3)39H2O:urea:NH4F=2~3:1:8~12:8~12.
[0031] It should be noted that there is no restriction on the order of dissolution of Co(NO3)26H2O, Fe(NO3)39H2O, urea and NH4F, and there is no need to deliberately follow the order in S101 of this embodiment, as long as the molar ratio of Co(NO3)26H2O:Fe(NO3)39H2O:urea:NH4F=2~3:1:8~12:8~12.
[0032] The carbon cloth pretreatment includes: placing the carbon cloth in a nitric acid solution with a concentration of 0.5 to 4.0 mol / L, placing the carbon cloth in a 3.0 M nitric acid solution, and ultrasonically washing the carbon cloth at a temperature of 40 to 80 ° C for 2 to 6 hours. The impurities and pollutants on the surface of the carbon cloth can be effectively removed by the combined action of ultrasound and nitric acid solution. The carbon cloth is taken out of the nitric acid solution and ultrasonically washed in ultrapure water and ethanol for 1 hour respectively. By further cleaning the carbon cloth, the possible residual nitric acid solution and other impurities are removed, and the dehydration effect of ethanol is used to prepare for the subsequent chemical reaction. The washed carbon cloth is placed in an oven at 60 to 80 ° C and baked for 1 hour to complete the carbon cloth pretreatment. By removing the moisture and residual solvent on the carbon cloth, the surface of the carbon cloth is made drier and cleaner.
[0033] The pretreated carbon cloth is placed in the obtained transparent solution, and a hydrothermal reaction is carried out at 120°C to 160°C to obtain a precursor CoFe(OH)@CC, including: pouring the obtained transparent solution into a polytetrafluoroethylene-lined container in batches. The pretreated carbon cloth is placed in a polytetrafluoroethylene-lined container containing a transparent solution. The carbon cloth in the polytetrafluoroethylene-lined container is cleaned with ultrasound. The vibration of ultrasound can cause the chemical substances in the transparent solution to adhere more evenly to the surface of the carbon cloth, thereby improving the reaction efficiency. The polytetrafluoroethylene-lined container containing the carbon cloth and the transparent solution is placed in a stainless steel autoclave. The autoclave can provide a stable high-pressure environment, which is conducive to the hydrothermal reaction. The stainless steel autoclave is placed in an oven and a hydrothermal reaction is carried out at 120°C to 160°C for 5 to 10 hours. This temperature range is set according to the optimal conditions for the chemical reaction, aiming to promote the formation of cobalt iron hydroxide. In some possible embodiments, the hydrothermal reaction temperature is preferably 140°C and the duration is preferably 9 hours. After the hydrothermal reaction, the autoclave was cooled naturally to room temperature to avoid damage to the product caused by stress due to rapid cooling. The carbon cloth was rinsed with ethanol and deionized water in turn to remove the residue on the surface. The rinsed carbon cloth was placed in an oven and dried at 50-100°C for 8h to obtain the precursor CoFe(OH)@CC.
[0034] S102: Soak the precursor CoFe(OH)@CC in a second mixed solution of 2-methylimidazole and ethanol for 8 to 24 hours to obtain a precursor CoFe(OH)@CC with a ZIF coating layer, take it out and put it in an oven, store it at 40 to 80°C for 8 hours, and obtain the precursor CoFe(OH)@ZIF@CC.
[0035] The precursor CoFe(OH)@CC is placed in a second mixed solution of 2-methylimidazole and ethanol and soaked for 8 to 24 hours to obtain a precursor CoFe(OH)@CC with a ZIF coating layer, which is taken out and placed in an oven and stored at 40 to 80°C for 8 hours to obtain a precursor CoFe(OH)@ZIF@CC, including: dissolving 2-methylimidazole in a first mixed solution containing water and ethanol, ensuring that 2-methylimidazole is completely dissolved, and forming a second mixed solution. The mass ratio of 2-methylimidazole, water, and ethanol in the second mixed solution is 1:5 to 8:5 to 8. 3.284 grams of 2-methylimidazole can be weighed and dissolved in a first mixed solution containing 20 mL of water and 20 mL of ethanol, ensuring that 2-methylimidazole is completely dissolved, and forming a second mixed solution. The mass ratio of 2-methylimidazole, water, and ethanol in the second mixed solution is 1:5 to 8:5 to 8. The precursor CoFe(OH)@CC is placed in the second mixed solution, and the precursor CoFe(OH)@CC is soaked for 8 to 24 hours to obtain the precursor CoFe(OH)@CC with a ZIF coating layer. In this process, 2-methylimidazole reacts with the metal ions on the surface of the precursor CoFe(OH)@CC, thereby forming a uniform ZIF coating layer on the surface of the carbon cloth. After the soaking, the precursor CoFe(OH)@CC is taken out from the second mixed solution, placed in an oven, and stored at 40 to 80°C for 8 hours to obtain the precursor CoFe(OH)@ZIF@CC. The purpose of this step is to remove the residual solvent on the carbon cloth and make the ZIF coating layer on its surface more stable.
[0036] It should be noted that in the precursor CoFe(OH)@ZIF@CC, CoFe(OH) represents cobalt iron hydroxide, ZIF represents the zeolite imidazolate framework material coating layer, and CC represents the carbon cloth substrate.
[0037] S103: In a hydrogen-argon mixed gas, the phosphorus source and the precursor CoFe(OH)@ZIF@CC are subjected to a phosphating annealing treatment at 250° C. to 600° C. to obtain a CoP@CoFeP@CC electrocatalyst.
[0038] In some possible embodiments, the phosphorus source includes one or more of sodium hypophosphite (NaH2PO2), red phosphorus, white phosphorus, and phosphorus trichloride.
[0039] In a hydrogen-argon mixed gas, a phosphorus source and a precursor CoFe(OH)@ZIF@CC are subjected to a phosphating annealing treatment at 250°C to 600°C to obtain a CoP@CoFeP@CC electrocatalyst, including: placing a phosphorus source at an upstream position of a porcelain boat. Placing the precursor CoFe(OH)@ZIF@CC at a downstream position of the porcelain boat. Such a layout is conducive to the phosphorus vapor generated by the decomposition of the phosphorus source at high temperature and the precursor CoFe(OH)@ZIF@CC to fully contact and react. The porcelain boat containing the phosphorus source and the precursor CoFe(OH)@ZIF@CC is placed in a tubular furnace, and argon and hydrogen are introduced to form a hydrogen-argon mixed gas. Prevent the material from being oxidized by oxygen in the air during the high-temperature treatment process. The tubular furnace is heated at a rate of 3°C / min to 250°C to 600°C, and this temperature range is maintained for 2 to 5 hours, and a phosphating annealing treatment is performed to obtain a reaction system. In some possible implementations, the heating temperature of the phosphating annealing treatment is preferably 500° C., and the temperature holding time is preferably 5 hours. The reaction system is allowed to cool naturally to room temperature in an argon environment to obtain the CoP@CoFeP@CC electrocatalyst. This can avoid the stress caused by rapid cooling from damaging the product.
[0040] It should be noted that the CoP@CoFeP@CC electrocatalyst has a unique cobalt-iron-phosphorus composite structure and is attached to a carbon cloth substrate. CoP stands for cobalt phosphide, CoFeP stands for cobalt-iron-phosphorus composite structure, and CC stands for carbon cloth substrate.
[0041] Figure 2 This is an electron microscope image of the CoP@CoFeP@CC electrocatalyst provided in the embodiment of this application. Figure 2 The CoP@CoFeP@CC electrocatalyst shown. The prepared CoP@CoFeP@CC electrocatalyst exhibits a unique regular nanoflower wire composite morphology, which gives the catalyst a series of excellent performance characteristics. Specifically, the catalyst not only exhibits excellent durability, but also exhibits good electrochemical stability. In the electrochemical performance test, the electrocatalyst exhibited efficient and stable electrocatalytic performance in both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). At a current density of 10mA / cm 2 Under the conditions of , the overpotential of the catalyst in HER is only 73mV, while the overpotential in OER is 253mV. Both values indicate that the catalyst has low energy loss and high catalytic efficiency in these two reactions. In addition, the catalyst also exhibits excellent catalytic stability. No obvious degradation of the current was observed during the continuous test for up to 30h, which further proves that the catalyst has good stability and durability.
[0042] The raw materials of the CoP@CoFeP@CC electrocatalyst in this application are widely available and easy to obtain, which reduces the cost of raw materials in the production process. The preparation process is relatively simple, easy to implement, and suitable for large-scale batch production, which further reduces the production cost. The CoP@CoFeP@CC electrocatalyst in this application effectively exposes more active sites through a unique structural design, which helps to improve the catalytic efficiency of the catalyst. The starfish-like tentacle CoP / CoFeP / CC heterostructure constructed on a carbon cloth substrate not only increases the specific surface area of the catalyst, but also significantly improves its boundary electron transfer capacity, mass transfer capacity and hydrogen proton transfer capacity during water splitting. This unique design enables the catalyst to more fully utilize the active sites in the catalytic reaction, thereby greatly improving the catalytic activity and providing a more efficient and stable catalyst option for electrochemical applications.
[0043] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0044] It can be understood that all raw materials used in the embodiments of the present invention can be purchased commercially.
[0045] Example 1
[0046] Take a 1cm×1cm carbon cloth and use nitric acid solution with a concentration of 0.5-4.0mol / L, ultrapure water and ethanol for ultrasonic washing in turn, and each washing time is 30 minutes. The ultrasonically treated carbon cloth is placed in a 60℃ oven for 30 minutes to remove residual moisture and solvent. Mix 2mmol of Co(NO3)26H2O, 1mmol of Fe(NO3)39H2O, 10mmol of urea and 10mmol of NH4F in 30mL of ultrapure water and stir well until a transparent solution is obtained. Pour the obtained transparent solution into a 100mL polytetrafluoroethylene-lined container, and put the pretreated carbon cloth into the container and clean it with ultrasound. Seal the container and place it in a stainless steel autoclave, and perform a hydrothermal reaction in an oven at 130℃ for 8h. After the reaction is completed, let the autoclave cool naturally to room temperature. Take out the carbon cloth and rinse it with ethanol and deionized water in turn to remove residual ions on the surface. The rinsed carbon cloth was placed in an oven at 60°C and baked for 8 h to obtain the precursor CoFe(OH)@CC.
[0047] Weigh 3.284 g of 2-methylimidazole and dissolve it in a first mixed solution containing 20 mL of water and 20 mL of ethanol. Place the synthesized precursor CoFe(OH)@CC in the solution and soak for 18 h. Place the precursor CoFe(OH)@CC in an oven at 60 °C and bake for 8 h to obtain the precursor CoFe(OH)@ZIF@CC.
[0048] The phosphorus source and the obtained precursor CoFe(OH)@ZIF@CC were placed in the upstream and downstream positions of the porcelain boat, respectively. The porcelain boat was placed in a tubular furnace and argon was introduced as a protective gas. The tubular furnace was heated at a rate of 3°C / min until the temperature reached 300°C and maintained at this temperature for 2 hours for the phosphating reaction. After the reaction was completed, the reaction system was allowed to cool naturally to room temperature in an argon environment. The cooled sample was taken out to obtain the final CoP@CoFeP@CC electrocatalyst.
[0049] Figure 3 This is a long-term stability test diagram of the CoP@CoFeP@CC electrocatalyst in OER (oxygen evolution reaction) provided in the examples of this application. The horizontal axis represents time (s), ranging from 0 to 10000 seconds. This time period is the basis for observing the change in current density. The vertical axis represents the current density (mA / cm 2 ), the unit is milliampere per square centimeter. Current density is a physical quantity that describes the size of the current passing through a conductor per unit area. It is used here to measure the activity of electrochemical reactions. There is a red line segment in the center of the chart, marked with "j = 10mA / cm 2 ". This line segment indicates that under the conditions of Example 1, the current density remains unchanged at 10 mA per square centimeter.
[0050] Figure 4 This is a comparison diagram of X-ray diffraction of the CoP@CoFeP@CC electrocatalyst provided in the examples of the present application. Figure 4 The crystal structure of the prepared CoP@CoFeP@CC electrocatalyst was analyzed by X-ray diffraction technology. There are three different material labels above the chart: CoP / Co2Fe1P / CC, Co2Fe1P / CC, CoFe(OH). Each material has a corresponding XRD spectrum showing its crystal structure information. Figure 4 It also contains a series of vertical bars representing the X-ray intensity of different crystal planes. These bars are arranged according to their position on the X-axis, forming a graph called a scatter plot. Figure 4 This indicates that the two compounds, CoP and CoFeP, were successfully synthesized in this embodiment, and they formed a close composite structure with the carbon cloth substrate.
[0051] It should be noted that the chemical formula of the CoP@CoFeP@CC electrocatalyst in this application can also be written as CoP / Co2Fe1P / CC.
[0052] Example 2
[0053] Take a 1cm×1cm carbon cloth and use nitric acid solution with a concentration of 0.5-4.0mol / L, ultrapure water and ethanol for ultrasonic washing in turn, and each washing time is 30 minutes. The ultrasonically treated carbon cloth is placed in a 60℃ oven for 30 minutes to remove residual moisture and solvent. Mix 2mmol of Co(NO3)26H2O, 1mmol of Fe(NO3)39H2O, 10mmol of urea and 10mmol of NH4F in 30mL of ultrapure water and stir well until a transparent solution is obtained. Pour the obtained transparent solution into a 100mL polytetrafluoroethylene-lined container, and put the pretreated carbon cloth into the container and clean it with ultrasound. Seal the container and place it in a stainless steel autoclave, and perform a hydrothermal reaction in an oven at 130℃ for 8h. After the reaction is completed, let the autoclave cool naturally to room temperature. Take out the carbon cloth and rinse it with ethanol and deionized water in turn to remove residual ions on the surface. The rinsed carbon cloth was placed in an oven at 60°C and baked for 8 h to obtain the precursor CoFe(OH)@CC.
[0054] Weigh 3.284 g of 2-methylimidazole and dissolve it in a first mixed solution containing 20 mL of water and 20 mL of ethanol. Place the synthesized precursor CoFe(OH)@CC in the solution and soak for 18 h. Place the precursor CoFe(OH)@CC in an oven at 60 °C and bake for 8 h to obtain the precursor CoFe(OH)@ZIF@CC.
[0055] The phosphorus source and the obtained precursor CoFe(OH)@ZIF@CC were placed in the upstream and downstream positions of the porcelain boat, respectively. The porcelain boat was placed in a tubular furnace and argon was introduced as a protective gas. The tubular furnace was heated at a rate of 3°C / min until the temperature reached 400°C and maintained at this temperature for 2 hours for the phosphating reaction. After the reaction was completed, the reaction system was allowed to cool naturally to room temperature in an argon environment. The cooled sample was taken out to obtain the final CoP@CoFeP@CC electrocatalyst.
[0056] Example 3
[0057] Take a 1cm×1cm carbon cloth and use nitric acid solution with a concentration of 0.5-4.0mol / L, ultrapure water and ethanol for ultrasonic washing in turn, and each washing time is 30 minutes. The ultrasonically treated carbon cloth is placed in a 60℃ oven for 30 minutes to remove residual moisture and solvent. Mix 2mmol of Co(NO3)26H2O, 1mmol of Fe(NO3)39H2O, 10mmol of urea and 10mmol of NH4F in 30mL of ultrapure water and stir well until a transparent solution is obtained. Pour the obtained transparent solution into a 100mL polytetrafluoroethylene-lined container, and put the pretreated carbon cloth into the container and clean it with ultrasound. Seal the container and place it in a stainless steel autoclave, and perform a hydrothermal reaction in an oven at 130℃ for 8h. After the reaction is completed, let the autoclave cool naturally to room temperature. Take out the carbon cloth and rinse it with ethanol and deionized water in turn to remove residual ions on the surface. The rinsed carbon cloth was placed in an oven at 60°C and baked for 8 h to obtain the precursor CoFe(OH)@CC.
[0058] Weigh 3.284 g of 2-methylimidazole and dissolve it in a first mixed solution containing 20 mL of water and 20 mL of ethanol. Place the synthesized precursor CoFe(OH)@CC in the solution and soak for 18 h. Place the precursor CoFe(OH)@CC in an oven at 60 °C and bake for 8 h to obtain the precursor CoFe(OH)@ZIF@CC.
[0059] The phosphorus source and the obtained precursor CoFe(OH)@ZIF@CC were placed in the upstream and downstream positions of the porcelain boat, respectively. The porcelain boat was placed in a tubular furnace and argon was introduced as a protective gas. The tubular furnace was heated at a rate of 3°C / min until the temperature reached 500°C and maintained at this temperature for 2 hours for the phosphating reaction. After the reaction was completed, the reaction system was allowed to cool naturally to room temperature in an argon environment. The cooled sample was taken out to obtain the final CoP@CoFeP@CC electrocatalyst.
[0060] Example 4
[0061] Take a 1cm×1cm carbon cloth and use nitric acid solution with a concentration of 0.5-4.0mol / L, ultrapure water and ethanol for ultrasonic washing in turn, and each washing time is 30 minutes. The ultrasonically treated carbon cloth is placed in a 60℃ oven for 30 minutes to remove residual moisture and solvent. Mix 2mmol of Co(NO3)26H2O, 1mmol of Fe(NO3)39H2O, 10mmol of urea and 10mmol of NH4F in 30mL of ultrapure water and stir well until a transparent solution is obtained. Pour the obtained transparent solution into a 100mL polytetrafluoroethylene-lined container, and put the pretreated carbon cloth into the container and clean it with ultrasound. Seal the container and place it in a stainless steel autoclave, and perform a hydrothermal reaction in an oven at 130℃ for 8h. After the reaction is completed, let the autoclave cool naturally to room temperature. Take out the carbon cloth and rinse it with ethanol and deionized water in turn to remove residual ions on the surface. The rinsed carbon cloth was placed in an oven at 60°C and baked for 8 h to obtain the precursor CoFe(OH)@CC.
[0062] Weigh 3.284 g of 2-methylimidazole and dissolve it in a first mixed solution containing 20 mL of water and 20 mL of ethanol. Place the synthesized precursor CoFe(OH)@CC in the solution and soak for 18 h. Place the precursor CoFe(OH)@CC in an oven at 60 °C and bake for 8 h to obtain the precursor CoFe(OH)@ZIF@CC.
[0063] The phosphorus source and the obtained precursor CoFe(OH)@ZIF@CC were placed in the upstream and downstream positions of the porcelain boat, respectively. The porcelain boat was placed in a tubular furnace and argon was introduced as a protective gas. The tubular furnace was heated at a rate of 3°C / min until the temperature reached 600°C and maintained at this temperature for 2 hours for the phosphating reaction. After the reaction was completed, the reaction system was allowed to cool naturally to room temperature in an argon environment. The cooled sample was taken out to obtain the final CoP@CoFeP@CC electrocatalyst.
[0064] It should be noted that the size of the carbon cloth in the present application is not limited to 1 cm×1 cm, and this size is only used as an example.
[0065] Figure 5Schematic diagram of the LSV (linear sweep voltammetry) curves of HER (hydrogen evolution reaction) and OER (oxygen evolution reaction) of the CoP@CoFeP@CC electrocatalyst obtained in Example 1, Example 2, Example 3 and Example 4 respectively provided in the embodiments of the present application in 1.0M potassium hydroxide (KOH) alkaline solution. The figure on the left is HER, and the figure on the right is OER. The figure on the left and the figure on the right show the relationship between potential and current density at different temperatures (400°C, 500°C and 600°C). The color coding in the chart (blue, red, yellow) represents different temperature conditions. The HER starting potential of CoP@CoFeP@CC is usually low, indicating that the material can start the hydrogen evolution reaction at a lower potential. When a certain current density (such as 10mA / cm 2 ), the overpotential required for CoP@CoFeP@CC may be smaller, indicating that its HER catalytic activity is higher. With the increase of potential, the HER current density of CoP@CoFeP@CC gradually increases, indicating that it has good electron transfer ability and catalytic active sites. For OER, the starting potential of CoP@CoFeP@CC is relatively high because the oxygen evolution reaction is generally more difficult to proceed than the hydrogen evolution reaction. When a specific current density (such as 10mA / cm 2 ) may require a larger overpotential, but CoP@CoFeP@CC may still exhibit a lower overpotential compared with other catalysts, indicating that the OER catalytic activity is also better.
[0066] Although the present application provides method operation steps as described in the embodiments or flow charts, more or fewer operation steps may be included based on conventional or non-creative work. The order of steps listed in this embodiment is only one way of executing the steps among many, and does not represent the only execution order.
[0067] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit the present application. Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the present application.
Claims
1. A method for preparing a CoP@CoFeP@CC electrocatalyst, characterized in that: include: Dissolve Co(NO3)26H2O, Fe(NO3)39H2O, urea and NH4F in ultrapure water to obtain a transparent solution; pretreat the carbon cloth, place the pretreated carbon cloth in the obtained transparent solution, and perform a hydrothermal reaction at 120°C to 160°C to obtain a precursor CoFe(OH)@CC; The precursor CoFe(OH)@CC is immersed in a second mixed solution of 2-methylimidazole and ethanol for 8 to 24 hours to obtain a precursor CoFe(OH)@CC with a ZIF coating layer, which is taken out and placed in an oven and stored at 40 to 80° C. for 8 hours to obtain a precursor CoFe(OH)@ZIF@CC; In a hydrogen-argon mixed gas, the phosphorus source and the precursor CoFe(OH)@ZIF@CC were subjected to phosphating annealing at 250°C to 600°C to obtain the CoP@CoFeP@CC electrocatalyst.
2. The method for preparing the CoP@CoFeP@CC electrocatalyst according to claim 1, characterized in that: The carbon cloth pretreatment comprises: The carbon cloth is placed in a nitric acid solution with a concentration of 0.5 to 4.0 mol / L, and ultrasonically cleaned at a temperature of 40 to 80° C. for 2 to 6 hours; The carbon cloth was taken out from the nitric acid solution and ultrasonically cleaned in ultrapure water and ethanol for 1 h each; The washed carbon cloth was placed in an oven at 60-80°C and baked for 1 h to complete the carbon cloth pretreatment.
3. The method for preparing the CoP@CoFeP@CC electrocatalyst according to claim 1, characterized in that: The pretreated carbon cloth is placed in the obtained transparent solution, and a hydrothermal reaction is performed at 120° C. to 160° C. to obtain a precursor CoFe(OH)@CC, comprising: The obtained clear solution was poured into a polytetrafluoroethylene-lined container in batches; The pretreated carbon cloth was placed in a polytetrafluoroethylene-lined container containing a transparent solution; Cleaning carbon cloth in a PTFE-lined container using ultrasonic waves; A Teflon-lined container containing the carbon cloth and the transparent solution was placed in a stainless steel autoclave; Place the stainless steel autoclave in an oven and perform a hydrothermal reaction at 120°C to 160°C for 5 to 10 hours; After the hydrothermal reaction was completed, the autoclave was naturally cooled to room temperature; Rinse the carbon cloth with ethanol and deionized water in sequence to remove the residue on the surface; The washed carbon cloth was placed in an oven and dried at 50-100°C for 8 h to obtain the precursor CoFe(OH)@CC.
4. The method for preparing the CoP@CoFeP@CC electrocatalyst according to claim 1, characterized in that: The precursor CoFe(OH)@CC is immersed in a second mixed solution of 2-methylimidazole and ethanol for 8 to 24 hours to obtain a precursor CoFe(OH)@CC with a ZIF coating layer, which is taken out and placed in an oven and stored at 40 to 80° C. for 8 hours to obtain a precursor CoFe(OH)@ZIF@CC, comprising: Dissolving 2-methylimidazole in a first mixed solution containing water and ethanol, ensuring that the 2-methylimidazole is completely dissolved, to form a second mixed solution; The mass ratio of 2-methylimidazole, water and ethanol in the second mixed solution is 1:5-8:5-8; Put the precursor CoFe(OH)@CC into the second mixed solution, and soak the precursor CoFe(OH)@CC for 8 to 24 hours to obtain the precursor CoFe(OH)@CC with a ZIF coating layer; After the immersion, the precursor CoFe(OH)@CC was taken out from the second mixed solution, put into an oven, and stored at 40-80°C for 8 hours to obtain the precursor CoFe(OH)@ZIF@CC.
5. The method for preparing the CoP@CoFeP@CC electrocatalyst according to claim 1, characterized in that: The method comprises: subjecting a phosphorus source and a precursor CoFe(OH)@ZIF@CC to a phosphating annealing treatment at 250° C. to 600° C. in a hydrogen-argon mixed gas to obtain a CoP@CoFeP@CC electrocatalyst. The method comprises: Place the phosphorus source upstream of the porcelain boat; Place the precursor CoFe(OH)@ZIF@CC at the downstream position of the porcelain boat; The porcelain boat containing the phosphorus source and the precursor CoFe(OH)@ZIF@CC was placed in a tubular furnace, and argon and hydrogen were introduced to form a hydrogen-argon mixed gas; The tubular furnace is heated at a rate of 3°C / min to a temperature of 250°C to 600°C, and the temperature is maintained in the range of 2 to 5 hours to perform phosphating annealing treatment to obtain a reaction system; The reaction system was allowed to cool naturally to room temperature in an argon environment to obtain the CoP@CoFeP@CC electrocatalyst.
6. The method for preparing the CoP@CoFeP@CC electrocatalyst according to claim 1, characterized in that: The molar ratio in the transparent solution is Co(NO3)26H2O:Fe(NO3)39H2O:urea:NH4F=2~3:1:8~12:8~12.
7. The method for preparing the CoP@CoFeP@CC electrocatalyst according to claim 1, characterized in that: The phosphorus source includes one or more of NaH2PO2, red phosphorus, white phosphorus, and phosphorus trichloride.
8. A CoP@CoFeP@CC electrocatalyst, characterized in that: The CoP@CoFeP@CC electrocatalyst is obtained by the preparation method according to any one of claims 1 to 7.